Adelė Dirsytė’s Pedagogical Work (1939–1946) - Grickevičius, Artūras (Genocidas ir rezistencija, 2019)
The pedagogical work of Adelė Dirsytė, a teacher and resister, who is titled “God Maid” by the Lithuanian Catholic Church has not been so far analysed separately at a scientific level. The only one work (at the same time – a publicist work as well) on this subject is the book “Adelė Dirsytė: her life and work”, compiled by Dr. Mindaugas Bloznelis, Vilnius: Academy of the Catholics, 2003“. Yet, in this source, the pedagogic path of the hero of this article is described too narrowly, inaccurately, or (in any cases) misleadingly. Administrative and court documents present at the Central State Archive of Lithuania and Special Archive of Lithuania allow analysing A. Dirsytė pedagogic work more thoroughly and describing it more accurately, while the testimonies of her class students and other pupils published assist in presenting expressly her character traits and merits as a teacher.• Dirsytė, within the period 1939-1946, worked in five educational institutions of different level. The first institution was Kaunas Society of the Holy Child Jesus Girls’ School of Crafts and Housework. At this school, she used to teach Lithuanian language those adolescent girls and young women that had acquired primary education. This work lasted from 26 January 1939 to 20 August 1940, i.e., until the moment of closing down the school; thus, she used to be a teacher during the times of Lithuanian Republic. The second school, where A. Dirsytė was employed as a teacher, was Vilnius Incomplete Secondary School of Adults. There, she taught German language those young adults, who had not acquired secondary education, among them there were young Poles and Jews as well, and she was a class mistress of one Lithuanian class too. There, she worked from 10 October 1940 until 1 August 1941, i.e., until the moment of closing down the school, thus, she was a teacher even during Sovietisation times. The third school, where A. Dirsytė worked as a teacher, – Vilnius State Secondary School of Crafts II, where she taught German and was a girls’ class mistress. In addition, she worked at Vilnius Institute of Adults – it was her fourth pedagogic employment place. This working period continued from 1 October 1941 to 15 June 1944, she used to work as a teacher even under conditions of the Nazi occupation regime. The fifth school, where A. Dirsytė was employed as a teacher was Vilnius Girls’ Gymnasium II, which in the autumn of 1945 was renamed and became Vilnius S. Nėris Gymnasium. There, she taught the German language and was the mistress of a Lithuanian class. In addition, he worked at Vilnius Folk University, i.e., at the reformed Vilniaus Institute of Adults, where she was an inspector or deputy director and a German language teacher. This working period covered the time from 16 September 1944 until 6 March 1946, i.e., until her arrest. At the time, she worked under conditions of the repeated Sovietization and harsh post-war conditions.• Dirsytė during her seven-year pedagogic activity encountered even four political systems. The teaching environment was influenced greatly by the change in political attitude, especially during the 1st and the 2nd Stalinist periods. Nevertheless, A. Dirsytė made every effort to perform well her duties like those of a Lithuania’s pedagogue and a member of a local Catholic community. During the first Stalinist occupation period, she avoided the work, related to Sovietization of schools, and resisted actively against some. During the Nazi period, as well as during the beginning of the second Stalinist period, she disseminated human values. In addition, at the time A. Dirsytė was acting for the sake of religion education of her students. The facts available demonstrate that she, when at Folk University, limited herself to performing her daily duties and disseminating cultural values, yet, while working at Girls‘ Gymnasium II or at S. Nėris Gymnasium, her work included assignments in the field of religion education, i.e., she openly encouraged church-going, used to teach religion secretly and, perhaps, indirectly promoted joining into community groups, practicing religion. Thus, she went beyond the norms and limits of pedagogics, set by the regime. The activity of such type, when attitudes, improper in the eyes of authorities, especially unsanctioned initiatives, used to be valued as adverse ones, was distinguished and very risky. Thus, the teacher A. Dirsytė should be valued as a passive resister, acting against Sovietization of schools, where she was working, and active resister, acting against atheism formation among her students.When discussing her personal traits, it should be pointed out, that A. Dirsytė was a balanced and modest person. When valuing her pedagogical properties, it shall be necessary to note that she was a dutiful, attentive, smart, diligent, having principles and consistent teacher and educationalist, who cared not only about good knowledge of the pupils, but also about their cultural education, especially – traditional value-based education. Her official educational work deserves attention and respect, especially unofficial pedagogic activity focused on religion education after the war. A. Dirsytė was slightly naively (perhaps) hoping that this work of hers and such activity were possible under conditions of Stalinist regime, yet her activity and pedagogic path throughout the post-war period in the aspect of Christian virtues should be valued as those of a Christ follower.
Keywords: Lithuania; Soviet occupation; German occupation; education; Adelė Dirsytė